2009
DOI: 10.1007/s00425-009-1006-3
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid stimulates secretion of the normally symplastic enzyme mannitol dehydrogenase: a possible defense against mannitol-secreting fungal pathogens

Abstract: The sugar alcohol mannitol is an important carbohydrate with well-documented roles in both metabolism and osmoprotection in many plants and fungi. In addition to these traditionally recognized roles, mannitol is reported to be an antioxidant and as such may play a role in host-pathogen interactions. Current research suggests that pathogenic fungi can secrete mannitol into the apoplast to suppress reactive oxygen-mediated host defenses. Immunoelectron microscopy, immunoblot, and biochemical data reported here s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 64 publications
1
38
0
Order By: Relevance
“…It has been demonstrated that proteins without signal peptide, such as celery mannitol dehydrogenase in A. thaliana , traffic to the apoplast while bypassing the classical ER/Golgi secretion pathway [56]. Another example is the hygromycin phosphotransferase in A. thaliana , which is secreted through a Golgi-independent route mediated by the Golgi-localized synaptotagmin 2 [57].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that proteins without signal peptide, such as celery mannitol dehydrogenase in A. thaliana , traffic to the apoplast while bypassing the classical ER/Golgi secretion pathway [56]. Another example is the hygromycin phosphotransferase in A. thaliana , which is secreted through a Golgi-independent route mediated by the Golgi-localized synaptotagmin 2 [57].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas clear functions have been ascribed to this form of unconventional secretion in mammals, such as recycling of transferrin and its receptor (Harding et al, 1984;Pan et al, 1985) and antigen presentation (Denzer et al, 2000;Van Niel et al, 2003), the nature of the molecules released through multivesicular body-PM fusion in plants in still unclear, although there seems to be a connection to the plant pathogen response . In this regard, EXPO-mediated exocytosis might be responsible for the secretion of apoplastic mannitol dehydrogenase upon salicylic acid treatment in plant cells (Cheng et al, 2009).…”
Section: Expos and Exosomes: Agents Of Unconventional Secretionmentioning
confidence: 99%
“…1,2 In other words, some extracellular proteins have been discovered that do not make use of the classical signal peptide-dependent secretory pathway. In plants, non-classical secretion has been poorly explored, although Cheng et al 3 have provided evidence on the salycilic acid-induced secretion of mannitol dehydrogenase, a normally symplastic enzyme, using a non-Golgi dependent pathway. In fact, plant non-classical protein secretion is recognized taking into account the large number of leaderless proteins detected in extracellular compartments, and has recently been discussed based on the concepts developed in other eukaryotic systems.…”
mentioning
confidence: 99%